Biochemical and demographical study of lipid profile in sera of patientswith gallstone
Thirty patients with gallstone [aged 25-55 years]and thirty age-and sex-matchedhealthy subjects as control group were involved. Those patients were intended toundergo surgical removal of gallbladder in the surgical ward- Al Sadder TeachingHospital and AL-Hakeem Hospital in Najaf city during the period from July/2009 toDecember /2009. The proportion of female was [86%] compared to the male t[14%]. The ratio of female: male was 5:1. Blood samples were obtained from allpatients prior to surgery. Serum was obtained by usual methods and analyzed forlipid profile test [total cholesterol [TC], triglyceride [TG], high density lipoprotein-cholesterol [HDL-C], low density lipoprotein cholesterol [LDL-C] and very lowdensity lipoprotein cholesterol [VLDL-C]